IL CONVEGNO AICA DEL 1984. LA PRESIDENZA HĂULICĂ E LA QUESTIONE DEI MARMI DEL PARTENONE - DIAMANTIS, Alexandros (Studia Universitatis Babeș-Bolyai Historia Artium, 2020)
The 1984 Conference of the International Association of Art Critics. The Presidency of Dan Hăulică and the Issue of the Parthenon Sculptures. In 1984, the Conference of the International Association of Art Critics (AICA), chaired by the Romanian Dan Hăulică (1932-2014), was organized for the first time in Greece; the event offered an opportunity for historians and art critics of various nationalities to meet. The theme of the conference, „Contemporary art and the Greek world. The XXth century in the face of the civilizations that have followed one another in the Greek space”, on the one hand honored the host country and on the other, placing the accent on the relationship between XXth century art and the Western artistic tradition, was part of the international discussion on the end of the avant-gardes. The complex relationships between the ancient and the contemporary were discussed in terms of influences, continuity and discontinuity. Particular attention was paid to the concept of myth and the mythical dimension of contemporary art. On the other hand, the generic definition of „Greek world", intentionally chosen by the Greek section of the AICA, re-proposed the national narrative of an essentially unitary historical-artistic development. The Conference also had a dimension of international political significance connected to the fact that the previous year the AICA, an organization affiliated with UNESCO, had approved a motion for the return to Greece of the Parthenon marbles kept at the British Museum. In Athens, the confirmation of solidarity with the Greek cause was also a matter of electoral campaign for the renewal of the Presidency of the AICA. REZUMAT. Conferința Asociației Internaționale a Criticilor de Artă din 1984. Președinția lui Dan Hăulică și chestiunea sculpturilor de la Parthenon. În anul 1984 Conferința Asociației Internaționale a Criticilor de Artă, prezidată de românul Dan Hăulică (1932-2014) a fost organizată pentru prima dată în Grecia; evenimentul a dat posibilitatea istoricilor și criticilor de artă din toată lumea, să se întâlnească. Tema conferinței „Arta contemporană și lumea grecească. Secolul XX și civilizațiile care s-au succedat în spațiul grecesc”, a onorat pe deoparte țara gazdă, iar pe de altă parte, punând accentul pe relația dintre arta secolului XX și tradiția artistică occidentală, a fost parte a discuției internaționale despre sfârșitul avangardei. Relațiile complexe dintre antic și contemporan au fost dezbătute în termeni de influențe, continuitate și discontinuitate. O atenție deosebită a fost acordată conceptului de mit și dimensiunii mitice a artei contemporane. Pe de altă parte, definiția generică a „lumii grecești”, aleasă intenționat de secțiunea grecească a AICA, repropunea discursul național în ansamblul dezvoltării istorico-artistice. Conferința a avut și o dimensiune internațională cu semnificație politică, legată de faptul că în anul anterior AICA, o organizație afiliată la UNESCO, a aprobat moțiunea pentru retrocedarea sculpturilor Parthenonului, aflate la British Museum, către Grecia. Confirmarea solidarității cu cauza Greciei, a reprezentat la Atena și o chestiune de campanie electorală pentru reînnoirea președinției AICA. Cuvinte cheie: conferința AICA, discursul artei, arta contemporană, marmura Parthenonului, patrimoniu clasic, mit, Dan Hăulică